Polyester film and method for producing the same
By combining the silicone chain content and silicone-free chain content modification products in the release layer of the polyester film, the problem of changing the peeling force during the peeling process is solved, and the stability and mechanical properties of the polyester film are improved at different peeling speeds.
Patent Information
- Application Number
- JP2023144299
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
AI Technical Summary
When the existing polyester film is used as a release film, the peeling force is easily changed due to the change in the peeling speed, and a stable peeling force is required in some applications.
A polyester film containing silicone chain content and silicone-free chain content modification products is used, the thickness of the -release layer is between 2 and 65 nm, the logarithmic damping rate is no more than 0.05, and the surface free energy is between 16 and 30 mJ/m². A combination of a specific silicone chain content and silicone-free chain content modification products is formed to form a polyester film with low peeling force dependence and good mechanical properties.
The peeling force stability of the polyester film at different peeling speeds is achieved, and the reliability and application performance of the polyester film in the manufacturing process is improved.
Smart Images

Figure 2025037391000001 
Figure 2025037391000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester film and a method for producing the same. [Background technology]
[0002] Polyester films are used in a variety of applications, such as films for touch panels, films for optical members, substrates for molding, substrates for decorative films, and substrates for photosensitive layers.
[0003] One of the uses of polyester films is as a release film, specifically, a release layer is provided on a polyester substrate, various members are produced in contact with the release layer, and then the members are released. For example, Patent Document 1 discloses a silicone release polyester film having a coating layer formed from a composition containing a specific silicone compound, a specific emulsifier, and the like, as a release film. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2021-011081 Summary of the Invention [Problem to be solved by the invention]
[0005] When a polyester film is used as a release film, it is sometimes required that the release force is less likely to change depending on the peeling speed, that is, that the peeling force has low dependency on the peeling speed. The present inventors have studied the polyester film described in Patent Document 1 and found that the peeling force may vary depending on the peeling speed, and that this issue needs to be improved.
[0006] Therefore, an object of the present invention is to provide a polyester film having a peel force that is less dependent on the peel speed. Another object of the present invention is to provide a method for producing a polyester film. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems, and have completed the present invention. That is, they have found that the above problems can be solved by the following configuration.
[0008] [1] A polyester film comprising a release layer and a polyester substrate, The release layer of the polyester film comprises a silicone chain-containing cured material and a silicone chain-free cured material. [2] The polyester film according to [1], wherein the release layer has a thickness of 2 to 65 nm. [3] The polyester film according to [1] or [2], wherein the release layer has a logarithmic decrement of 0.05 or less. [4] The surface free energy of the surface of the release layer is 16 mJ / m 2 More than 30mJ / m 2 The polyester film according to any one of [1] to [3], wherein the thickness of the polyester film is less than 100 nm. [5] The polyester film according to any one of [1] to [4], wherein the silicone chain-containing cured product is a cured product of a composition A containing a silicone compound having a vinyl group and a silicone compound having a SiH group. [6] The polyester film according to any one of [1] to [5], wherein the silicone chain-free cured product is a cured product of a composition C containing one or more crosslinking agents selected from the group consisting of oxazoline compounds, isocyanate compounds, carbodiimide compounds, melamine compounds, and epoxy compounds. [7] The polyester film according to [6], wherein the composition C further contains a non-silicone resin that crosslinks with the crosslinking agent. [8] The polyester film according to [7], wherein the non-silicone resin comprises a resin selected from the group consisting of an acrylic resin, a urethane resin, and an olefin resin. [9] The silicone chain-free cured product is a cured product of a composition C containing one or more crosslinking agents selected from the group consisting of oxazoline compounds, carbodiimide compounds, and isocyanate compounds; The polyester film according to [7] or [8], wherein the ratio of the content of the non-silicone resin to the content of the crosslinking agent is 0.3 to 2.0.
[10] The polyester film according to any one of [1] to [9], wherein the polyester base material is substantially free of inorganic particles.
[11] The polyester film according to any one of [1] to
[10] , wherein the release layer has a maximum protrusion height on the surface of the release layer of 30 nm or less.
[12] The polyester film according to any one of [1] to
[11] , which has a dynamic friction coefficient of 0.2 or more.
[13] The polyester film according to any one of [1] to
[12] , which is used for producing a ceramic green sheet.
[14] A method for producing a polyester film comprising a release layer and a polyester substrate, comprising: A method for producing a polyester film, comprising the step of applying a composition containing a component that forms a silicone chain-containing cured product and a component that forms a silicone chain-free cured product to one surface of the polyester substrate.
[15] The method for producing a polyester film according to
[14] , wherein the composition contains water. Effect of the Invention
[0009] According to the present invention, a polyester film having a peel force with low dependency on peel speed can be provided. The present invention also provides a method for producing a polyester film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below. The following description of the configuration may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment.
[0011] The following describes the meaning of each description in this specification. In this specification, a numerical range expressed using "~" means a range including the numerical values described before and after "~" as the lower and upper limits. In the numerical ranges described in stages in this specification, the upper or lower limit described in a certain numerical range may be replaced with the upper or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in this specification, the upper or lower limit described in a certain numerical range may be replaced with a value shown in the examples. In this specification, the amount of each component in a composition means the total amount of multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. In this specification, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved. As used herein, a combination of two or more preferred embodiments is a more preferred embodiment.
[0012] In this specification, the term "longitudinal direction" refers to the longitudinal direction of a film during its production, and is synonymous with the terms "conveyance direction" and "machine direction." In this specification, the "width direction" refers to a direction perpendicular to the longitudinal direction. In this specification, "perpendicular" is not limited to strictly perpendicular, but includes approximately perpendicular. "Approximately perpendicular" means intersecting within a range of 90°±5°, preferably within a range of 90°±3°, and more preferably within a range of 90°±1°.
[0013] [Polyester film] The polyester film of the present invention includes a release layer and a polyester substrate, wherein the release layer includes a silicone chain-containing cured material and a silicone chain-free cured material. In the polyester film of the present invention, the mechanism by which the peel force has a low peel rate dependency is not entirely clear, but the present inventors speculate as follows. In the polyester film of the present invention, since the release layer contains a silicone chain-containing cured material, the surface free energy on the surface of the release layer (the surface of the release layer opposite the polyester substrate, hereinafter also referred to as the "release surface") tends to be low, and the peel force tends to be small. On the other hand, since the release layer in the polyester film of the present invention contains a silicone chain-free cured product, the release layer becomes hard and is less likely to deform, and therefore, when the above-mentioned member is peeled off, the release layer is less likely to deform following the above-mentioned member, etc. Therefore, in the polyester film of the present invention, the peel force at the release surface is small and the release layer is less likely to deform, which is believed to result in low dependency of the peel force on the peel speed. The components contained in the polyester film of the present invention will be described below. Hereinafter, the polyester film of the present invention will also be referred to as "the film".
[0014] <Polyester base material> The polyester substrate is a film-like object containing a polyester resin as a main component. Here, the "main component" refers to the component that is contained in the largest amount (by mass) among all the components contained in the film-like object.
[0015] As the polyester substrate, a biaxially oriented polyester substrate is preferred. "Biaxial orientation" means a property of having molecular orientation in two axial directions. The molecular orientation is measured using a microwave transmission type molecular orientation meter (e.g., MOA-6004, manufactured by Oji Scientific Instruments Co., Ltd.). The angle between the two axial directions is preferably within the range of 90°±5°, more preferably within the range of 90°±3°, and even more preferably within the range of 90°±1°. The molecular orientation changes when the film is stretched, and a biaxially oriented polyester substrate can be produced by performing biaxial stretching.
[0016] It is preferable that the polyester substrate is substantially free of inorganic particles. "Substantially free of inorganic particles" is defined as the content of inorganic particles being 50 mass ppm or less, preferably 10 mass ppm or less, more preferably below the detection limit, relative to the total mass of the polyester substrate when elements derived from inorganic particles are quantitatively analyzed by fluorescent X-ray analysis. This is because even if inorganic particles are not actively added to the polyester substrate, contaminants derived from foreign matter, raw material resin, or dirt attached to the line or equipment in the manufacturing process of the polyester substrate may peel off and be mixed into the polyester substrate. Examples of the inorganic particles include inorganic particles that may be contained in the particle-containing layer (protrusion-containing layer) described below.
[0017] (polyester resin) The polyester resin contained in the polyester base material is a polymer having an ester bond in the main chain, and is usually formed by polycondensation of a dicarboxylic acid compound and a diol compound, which will be described later. The polyester resin is not particularly limited, and known polyester resins can be used. Examples of the polyester resin include polyethylene terephthalate (PET), polypropylene terephthalate (PPT), polybutylene terephthalate (PBT), polyethylene-2,6-naphthalate (PEN), and copolymers thereof, with PET, PEN, and copolymers thereof being preferred, and PET being more preferred.
[0018] The intrinsic viscosity of the polyester resin is preferably 0.50 dl / g or more and less than 0.80 dl / g, and more preferably 0.55 dl / g or more and less than 0.70 dl / g. The melting point (Tm) of the polyester resin is preferably from 220 to 270°C, and more preferably from 245 to 265°C. The glass transition temperature (Tg) of the polyester resin is preferably from 65 to 90°C, and more preferably from 70 to 85°C.
[0019] The method for producing the polyester resin is not particularly limited, and a known method can be used. For example, the polyester resin can be produced by polycondensing at least one dicarboxylic acid compound and at least one diol compound in the presence of a catalyst.
[0020] -catalyst- The catalyst used in the production of the polyester resin is not particularly limited, and any known catalyst that can be used in the synthesis of polyester resins can be used. Examples of the catalyst include alkali metal compounds (e.g., potassium compounds, sodium compounds), alkaline earth metal compounds (e.g., calcium compounds, magnesium compounds), zinc compounds, lead compounds, manganese compounds, cobalt compounds, aluminum compounds, antimony compounds, titanium compounds, germanium compounds, and phosphorus compounds. Among these, titanium compounds and aluminum compounds are preferred because they are less likely to cause foreign matter and voids in the polyester substrate. The catalyst may be used alone or in combination of two or more. It is also preferable to use at least one metal catalyst selected from potassium compounds, sodium compounds, calcium compounds, magnesium compounds, zinc compounds, lead compounds, manganese compounds, cobalt compounds, aluminum compounds, antimony compounds, titanium compounds, and germanium compounds in combination with a phosphorus compound.
[0021] The titanium compound is preferably an organic chelate titanium complex, which is a titanium compound having an organic acid as a ligand. Examples of organic acids include citric acid, lactic acid, trimellitic acid, and malic acid. As the titanium compound, the titanium compounds described in
[0049] to
[0053] of Japanese Patent No. 5575671 can also be used, and the contents of the above publication are incorporated herein by reference.
[0022] Examples of the aluminum compound include organoaluminum compounds and their partial hydrolysates. The organoaluminum compound is preferably a carboxylate, an inorganic acid salt, or a chelate compound, and more preferably aluminum acetate, basic aluminum acetate, aluminum lactate, aluminum chloride, aluminum hydroxide, aluminum hydroxide chloride, or aluminum acetylacetonate.
[0023] -Dicarboxylic acid compounds- Examples of the dicarboxylic acid compound include dicarboxylic acids such as aliphatic dicarboxylic acid compounds, alicyclic dicarboxylic acid compounds, and aromatic dicarboxylic acid compounds, as well as dicarboxylic acid esters such as methyl ester compounds and ethyl ester compounds of these dicarboxylic acids. Among these, aromatic dicarboxylic acids or aromatic methyl dicarboxylates are preferred.
[0024] Examples of the aliphatic dicarboxylic acid compound include malonic acid, succinic acid, glutaric acid, adipic acid, suberic acid, sebacic acid, dodecanedioic acid, dimer acid, eicosanedioic acid, pimelic acid, azelaic acid, methylmalonic acid, and ethylmalonic acid. Examples of the alicyclic dicarboxylic acid compound include adamantanedicarboxylic acid, norbornenedicarboxylic acid, cyclohexanedicarboxylic acid, and decalindicarboxylic acid.
[0025] Examples of aromatic dicarboxylic acid compounds include terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 5-sodiumsulfoisophthalic acid, phenylindanedicarboxylic acid, anthracenedicarboxylic acid, phenanthrenedicarboxylic acid, and 9,9'-bis(4-carboxyphenyl)fluorene acid. Among these, terephthalic acid or 2,6-naphthalenedicarboxylic acid is preferred, and terephthalic acid is more preferred.
[0026] The dicarboxylic acid compound may be used alone or in combination of two or more. When terephthalic acid is used as the dicarboxylic acid compound, terephthalic acid may be used alone or may be copolymerized with other aromatic dicarboxylic acids such as isophthalic acid or aliphatic dicarboxylic acids.
[0027] -Diol compounds- Examples of the diol compound include an aliphatic diol compound, an alicyclic diol compound, and an aromatic diol compound, and an aliphatic diol compound is preferable.
[0028] Examples of the aliphatic diol compound include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,2-butanediol, 1,3-butanediol, and neopentyl glycol, and ethylene glycol is preferred. Examples of the alicyclic diol compound include cyclohexanedimethanol, spiroglycol, and isosorbide. Examples of aromatic diol compounds include bisphenol A, 1,3-benzenedimethanol, 1,4-benzenedimethanol, and 9,9'-bis(4-hydroxyphenyl)fluorene. The diol compound may be used alone or in combination of two or more kinds.
[0029] -End capping agent- In the production of the polyester resin, a terminal capping agent may be used as necessary. By using the terminal capping agent, a structure derived from the terminal capping agent is introduced into the terminal of the polyester resin. The terminal blocking agent is not limited, and any known terminal blocking agent can be used. Examples of the terminal blocking agent include oxazoline compounds, carbodiimide compounds, and epoxy compounds. For the terminal blocking agent, reference can also be made to the contents described in paragraphs
[0055] to
[0064] of JP2014-189002A, the contents of which are incorporated herein by reference.
[0030] -Manufacturing conditions- The reaction temperature is not limited and may be appropriately set depending on the raw materials. The reaction temperature is preferably 260 to 300°C, more preferably 275 to 285°C. The pressure is not limited and may be set appropriately depending on the raw materials. The pressure is 1.33×10 -3 ~1.33×10 -5 MPa is preferred, 6.67 x 10 -4 ~6.67×10 -5 MPa is more preferred.
[0031] As a method for synthesizing the polyester resin, the method described in paragraphs
[0033] to
[0070] of Japanese Patent No. 5575671 can also be used, and the contents of the above publication are incorporated herein by reference.
[0032] The content of the polyester resin in the polyester base material is preferably 85% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and particularly preferably 98% by mass or more, based on the total mass of the polyester base material. The upper limit of the content of the polyester resin is not limited, and can be appropriately set within the range of less than 100% by mass with respect to the total mass of the polyester base material.
[0033] When the polyester base material contains polyethylene terephthalate, the content of polyethylene terephthalate is preferably 90 to 100 mass%, more preferably 95 to 100 mass%, still more preferably 98 to 100 mass%, and particularly preferably 100 mass%, based on the total mass of the polyester resin in the polyester base material.
[0034] The polyester base material may contain components other than the polyester resin (for example, a catalyst, unreacted raw material components, particles, water, etc.).
[0035] The thickness of the polyester substrate is preferably 200 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, still more preferably 40 μm or less, and particularly preferably 35 μm or less. There is no particular lower limit to the thickness, but in terms of improving strength and processability, it is preferably 1 μm or more, more preferably 3 μm or more, even more preferably 10 μm or more, and particularly preferably 20 μm or more. The thickness of the polyester substrate is defined as the arithmetic average value of the thicknesses of five points of the polyester substrate in a slice prepared by preparing a slice having a cross section perpendicular to the main surface of the polyester film and measuring the thicknesses of the polyester substrate in the slice using a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0036] <Release layer> The release layer is a layer disposed on one side of the polyester substrate. When the present film is used as a release film, various members are produced in contact with the release layer, and then the members are peeled off. In this film, the release layer contains a silicone chain-containing cured material and a silicone chain-free cured material. The silicone chain-containing cured product and the silicone chain-free cured product, as well as the components that may be contained in the release layer, will be described below.
[0037] (Silicone chain-containing cured product) The release layer contains a silicone chain-containing cured material. In this specification, the silicone chain-containing cured material refers to a polymer compound containing a silicone chain formed by a series of siloxane bonds represented by Si-O-Si. In this specification, the term "silicone compound" refers to a compound having a silicone chain, and the term "silicone resin" refers to a resin having a silicone chain. The silicone chain may, for example, have a chain structure formed by bonding repeating units represented by the following formula (1).
[0038] [ka]
[0039] In formula (1), R each independently represents a hydrogen atom or an organic group. Examples of the organic group include a hydrocarbon group which may have a substituent. Examples of the hydrocarbon group moiety of the hydrocarbon group which may have a substituent include an alkyl group and an aryl group. In addition, R may be bonded to another silicone chain or a group bonded to another silicone chain in the silicone chain-containing cured product. The silicone chain may contain two or more repeating units represented by the above formula (1). In the silicone chain, the number of repeating units represented by the above formula (1) is preferably 5 or more, more preferably 20 or more, and even more preferably 50 or more. There is no particular upper limit, but it is preferably 2500 or less, more preferably 2000 or less, and even more preferably 1000 or less. In addition, in the above formula (1), the organic group may be a group having a silicone chain, that is, the silicone chain may be either linear or branched.
[0040] The silicone chain-containing cured product is not particularly limited as long as it contains a silicone chain. For example, the silicone chain-containing cured product is preferably a cured product of a reactive curable silicone resin. Examples of the reactive curable silicone resin include an addition reaction silicone resin, a condensation reaction silicone resin, and an ultraviolet or electron beam curable silicone resin. The silicone chain-containing cured product is preferably a cured product of a first compound having an alkenyl group and a second compound having a hydrogen atom bonded to a silicon atom (-Si-H, also called a SiH group). At least one of the first compound and the second compound preferably has a silicone chain, and it is more preferable that the first compound and the second compound both have a silicone chain. The first compound and the second compound will be described below.
[0041] -First compound- The first compound includes a silicone compound having an alkenyl group and an alkenyl-containing crosslinking agent having two or more alkenyl groups in the molecule, and is preferably a silicone compound having an alkenyl group.As the silicone compound having an alkenyl group, a silicone compound having a vinyl group is preferred, and a silicone compound having a vinyl group introduced at least one of the terminal and the side chain is more preferred, and a polydimethylsiloxane having a vinyl group introduced at least one of the terminal and the side chain is more preferred.The polydimethylsiloxane having a vinyl group introduced at least one of the terminal and the side chain may be an oligomer or a resin.
[0042] Examples of the alkenyl group-containing crosslinking agent include a compound having two or more vinyl groups in the molecule, a compound having two or more allyl groups in the molecule, and a compound having two or more (meth)acryloyl groups in the molecule. Of these, a compound having two or more vinyl groups in the molecule or a compound having two or more allyl groups in the molecule is preferred. More specifically, the alkenyl group-containing crosslinking agent may be an ester compound (allyl ester compound) of a polycarboxylic acid compound having two or more carboxy groups in the molecule and allyl alcohol. Examples of the alkenyl group-containing crosslinking agent include vinyl ether compounds having two or more vinyl groups in the molecule. In addition, examples of the alkenyl group-containing crosslinking agent include ester compounds of a polyol compound having two or more hydroxyl groups in the molecule and acrylic acid or methacrylic acid. Note that the term "(meth)acryloyl group" refers to a concept including a methacryloyl group and an acryloyl group.
[0043] -Second compound- The second compound is preferably a silicone compound having a SiH group. Examples of the silicone compound having a SiH group include polydimethylsiloxane having a hydrogen atom bonded to a silicon atom introduced into at least one of the terminal and the side chain.
[0044] The content of the silicone chain-containing cured material in the release layer is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, based on the total mass of the release layer, in order to reduce the peeling speed dependency of the peeling force. The content of the silicone chain-containing cured material in the release layer is often 80% by mass or less, preferably 70% by mass or less, and more preferably 60% by mass or less, based on the total mass of the release layer.
[0045] The silicone chain-containing cured product can be formed, for example, by curing the first compound and the second compound using a method appropriate for the type of compound. Hereinafter, as an example, a silicone chain-containing cured product will be described as a cured product of a silicone compound having a vinyl group (first compound) and a silicone compound having a SiH group (second compound). Note that, hereinafter, the composition containing the silicone compound having a vinyl group and the silicone compound having a SiH group will also be referred to as "composition A".
[0046] The silicone chain-containing cured product can be formed by curing composition A. Composition A preferably contains a curing catalyst. The curing catalyst is preferably a catalyst that promotes a hydrosilylation reaction (hydrosilylation catalyst). The hydrosilylation catalyst is preferably a platinum group compound, more preferably a platinum compound.
[0047] The platinum compound is not particularly limited, but examples thereof include platinum halides (e.g., PtCl4, H2PtCl4·6H2O, Na2PtCl4·4H2O, and reaction products of H2PtCl4·6H2O and cyclohexane), platinum-olefin complexes, platinum-alcohol complexes, platinum-alcoholate complexes, platinum-ether complexes, platinum-aldehyde complexes, platinum-ketone complexes, and platinum-vinylsiloxane complexes (e.g., platinum-1,3 -divinyl 1,1,3,3-tetramethyldisiloxane complex, bis-(γ-picoline)-platinum dichloride, trimethylenedipyridine-platinum dichloride, dicyclopentadiene-platinum dichloride, cyclooctadiene-platinum dichloride, cyclopentadiene-platinum dichloride, bis(alkynyl)bis(triphenylphosphine)platinum complex, and bis(alkynyl)(cyclooctadiene)platinum complex.
[0048] Composition A may also contain additives such as a solvent and a surfactant.
[0049] (Silicone chain-free cured product) The release layer comprises a silicone chain-free cured material. In this specification, the silicone chain-free cured material refers to a cured material that does not contain the above-mentioned silicone chain. It is preferable that there is no covalent bond between the silicone chain-free cured material and the silicone chain-containing cured material, and that the silicone chain-free cured material and the silicone chain-containing cured material are different cured materials. There are no particular limitations on the silicone chain-free cured product, so long as it does not contain silicone chains. Among them, the silicone chain-free cured product is preferably a cured product obtained by curing a composition containing a crosslinking agent (hereinafter also referred to as "composition C"). Furthermore, composition C may contain a crosslinking agent and a non-silicone resin that crosslinks with the crosslinking agent. The crosslinking agent and the non-silicone resin will now be described.
[0050] -Crosslinking agent- The crosslinking agent is not particularly limited, and examples thereof include one or more crosslinking agents selected from the group consisting of oxazoline compounds, isocyanate compounds, carbodiimide compounds, melamine compounds, and epoxy compounds. Among these, one or more crosslinking agents selected from the group consisting of oxazoline compounds, carbodiimide compounds, and isocyanate compounds are preferred, since when a component is placed on the release layer and the component is peeled off, the amount of components derived from the release layer that migrate to the component is smaller, and oxazoline compounds, carbodiimide compounds, or isocyanate compounds are more preferred.
[0051] Oxazoline compounds The oxazoline compound is not particularly limited as long as it is a compound having an oxazoline group, and may be a low molecular weight compound having a weight average molecular weight of less than 1000, or a high molecular weight compound having a weight average molecular weight of more than 1000. However, a high molecular weight compound is preferable in that the release layer has better solvent resistance.
[0052] Examples of low molecular weight compounds having an oxazoline group include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 2-isopropenyl-5-methyl-2-oxazoline, 2-isopropenyl-5-ethyl-2-oxazoline, 2,2'-bis-(2-oxazoline), 2,2'-methylene-bis-(2-oxazoline), 2,2'-ethylene-bis-(2-oxazoline), 2,2'-trimethylene-bis- (2-oxazoline), 2,2'-tetramethylene-bis-(2-oxazoline), 2,2'-hexamethylene-bis-(2-oxazoline), 2,2'-octamethylene-bis-(2-oxazoline), 2,2'-ethylene-bis-(4,4'-dimethyl-2-oxazoline), 2,2'-p-phenylene-bis-(2-oxazoline), 2,2'-m-phenylene-bis-(2-oxazoline), 2,2'-m-phenylene-bis-(4,4'-dimethyl-2-oxazoline), bis-(2-oxazolinylcyclohexane)sulfide, and bis-(2-oxazolinylnorbornane)sulfide.
[0053] When the oxazoline compound is a polymeric compound, it is sufficient that the polymeric compound has an oxazoline group, and examples thereof include copolymers that contain the above-mentioned low molecular weight compound having an oxazoline group as a constituent unit.
[0054] The polymer compound having an oxazoline group is preferably a polymer containing an oxazoline group and a polyalkylene oxide chain, and more preferably an acrylic polymer containing an oxazoline group and a polyalkylene oxide chain.
[0055] The polymer compound having an oxazoline group is preferably a copolymer containing a structural unit derived from the above-mentioned low molecular weight compound having an oxazoline group and a structural unit derived from a (meth)acrylic acid ester containing a polyalkylene oxide chain.
[0056] Examples of the polyalkylene oxide chain include polymethylene oxide, polyethylene oxide, polypropylene oxide, and polybutylene oxide. The polyalkylene oxide chain preferably has 3 to 100 repeating units.
[0057] Examples of (meth)acrylic acid esters containing a polyalkylene oxide chain include methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, and ethoxypolypropylene glycol (meth)acrylate.
[0058] The polymer compound having an oxazoline group may contain a constituent unit derived from a low molecular weight compound having an oxazoline group and a constituent unit derived from a monomer other than the constituent unit derived from a (meth)acrylic acid ester containing a polyalkylene oxide chain.
[0059] Examples of other monomers include alkyl group-containing monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate; hydroxyl-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-hydroxypropyl (meth)acrylate; epoxy group-containing monomers such as glycidyl (meth)acrylate and allyl glycidyl ether; carboxyl group-containing monomers such as (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, and styrenesulfonic acid, and salts thereof (e.g., , sodium salts, potassium salts, ammonium salts, and tertiary amine salts); amide group-containing monomers such as (meth)acrylamide, N-alkyl(meth)acrylamide, N,N-dialkyl(meth)acrylamide, N,N-dialkyl(meth)acrylate (examples of alkyl groups: methyl group, ethyl group, n-butyl group, isobutyl group, etc.), acryloylmorpholine, N-methylol(meth)acrylamide, and N-phenyl(meth)acrylamide; acid anhydride monomers such as maleic anhydride and itaconic anhydride; vinyl isocyanate, allyl isocyanate, styrene, α-methylstyrene, vinyl methyl ether, vinyl ethyl ether, vinyl trialkoxysilane, alkyl maleic acid monoester, alkyl fumaric acid monoester, alkyl itaconic acid monoester, (meth)acrylonitrile vinylidene chloride, ethylene, propylene, vinyl chloride, vinyl acetate, and butadiene.
[0060] From the viewpoint of environmental load, the polymer compound having an oxazoline group is preferably water-soluble.
[0061] The weight average molecular weight of the polymer compound having an oxazoline group is not particularly limited, but is preferably 5,000 or more, more preferably 7,000 to 200,000, and even more preferably 10,000 to 150,000.
[0062] The polymer compound having an oxazoline group may be a commercially available product, such as EPOCROS (registered trademark, hereinafter the same) K-2010E, EPOCROS K-2020E, EPOCROS K-2030E, EPOCROS WS-700, and EPOCROS WS-300 (all manufactured by Nippon Shokubai Co., Ltd.).
[0063] When the above composition C contains an oxazoline compound, the composition C preferably contains a non-silicone resin described below, and the non-silicone resin preferably has a curable group described below.
[0064] ·Isocyanate compounds The isocyanate compound is preferably a blocked isocyanate compound. A blocked isocyanate compound is a compound in which the isocyanate group of a polyisocyanate is protected (ie, blocked) with a blocking agent, and is included in the isocyanate compound in this specification. Examples of blocking agents in blocked isocyanates include ester compounds, phenol compounds, alcohol compounds, oxime compounds, mercaptan compounds, lactam compounds, amine compounds, acid amide compounds, pyrazole compounds, triazole compounds, and bisulfite compounds.
[0065] Examples of the ester compound include malonic acid diesters such as dimethyl malonate and diethyl malonate, and acetoacetic acid esters such as methyl acetoacetate and ethyl acetoacetate. Among these, diethyl malonate is preferred from the viewpoint of availability. Examples of phenol compounds include phenol, o-cresol, m-cresol, p-cresol, 2,3-xylenol, 2,4-xylenol, 2,5-xylenol, 2,6-xylenol, 3,4-xylenol, 3,5-xylenol, and ethylphenol. Examples of the alcohol compound include methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, propylene glycol monomethyl ether, ethylene glycol, and benzyl alcohol. Examples of the oxime compound include acetoxime, methyl ethyl ketone oxime, acetaldoxime, formaldoxime, diacetyl monooxime, and cyclohexane oxime, and acetoxime or methyl ethyl ketone oxime is preferable.
[0066] Mercaptan compounds include butyl mercaptan and dodecyl mercaptan. Examples of lactam compounds include ε-caprolactam, δ-valerolactam, γ-butyrolactam, and β-propiolactam, with ε-caprolactam being preferred. Examples of the amine compound include diphenylaniline, aniline, and ethyleneimine. Examples of the acid amide compound include acetanilide and acetic acid amide. Examples of pyrazole compounds include methylpyrazole (e.g., 2-methylpyrazole, 3-methylpyrazole, 4-methylpyrazole), dimethylpyrazole (e.g., 2,4-dimethylpyrazole, 2,5-dimethylpyrazole, 3,4-dimethylpyrazole, 3,5-dimethylpyrazole), 4-nitro-3,5-dimethylpyrazole, and 4-bromo-3,5-dimethylpyrazole, with methylpyrazole or dimethylpyrazole being preferred. An example of the triazole compound is 1,2,4-triazole.
[0067] Examples of polyisocyanates in which the isocyanate group is protected by a blocking agent include polyfunctional polyisocyanates in the form of an adduct (also called an adduct body) obtained by adding 3 moles of diisocyanate to 1 mole of trimethylolpropane, a biuret (also called a biuret body) obtained by reacting 3 moles of diisocyanate with 1 mole of water, or an isocyanurate (also called an isocyanurate body) obtained by polymerization of 3 moles of diisocyanate. The polyisocyanate in which the isocyanate group is protected by a blocking agent may also be a polyurethane polyisocyanate obtained by reacting a polyisocyanate with a polyol (for example, a polyester polyol, a polyether polyol, or a low molecular weight polyol). Examples of diisocyanates include aromatic diisocyanates, aliphatic diisocyanates, and alicyclic isocyanates. From the viewpoint of producing a ceramic green sheet with reduced defects and without causing concave defects on the peeled surface, aliphatic diisocyanates are preferred, and hexamethylene diisocyanate is more preferred.
[0068] Examples of the diisocyanate include aromatic diisocyanates such as 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyl diisocyanate, tetraalkyldiphenylmethane diisocyanate, dialkyldiphenylmethane diisocyanate, 1,3-phenylene diisocyanate, polymeric diphenylmethane diisocyanate, tolylene diisocyanate (2,4- or 2,6-tolylene diisocyanate), 4,4'-toluidine diisocyanate, 4,4'diphenyl ether diisocyanate, 1,5-naphthylene diisocyanate, and naphthalene diisocyanate.
[0069] Examples of the diisocyanate include aliphatic diisocyanates, such as hexamethylene diisocyanate, trimethylene diisocyanate, trimethylhexamethylene diisocyanate (2,2,4- or 2,4,4-trimethylhexamethylene diisocyanate), lysine diisocyanate, xylylene diisocyanate, 1,2-propylene diisocyanate, butylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, and 1,5-pentamethylene diisocyanate.
[0070] Examples of diisocyanates include alicyclic isocyanates, such as 1,3-cyclopentane diisocyanate, 1,3 cyclopentene diisocyanate, cyclohexane diisocyanate (1,3- or 1,4-cyclohexane diisocyanate), 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, methylcyclohexane diisocyanate (-2,4- or -2,6-methylcyclohexane diisocyanate), and norbornane diisocyanate.
[0071] Among these, from the viewpoints of availability and ease of synthesis, an isocyanurate of hexamethylene diisocyanate, a biuret of hexamethylene diisocyanate, or an adduct of hexamethylene diisocyanate is preferred.
[0072] As the blocked isocyanate, a commercially available product may be used. Examples of commercially available products include 2554, 2507, and BI-301 from the Coronate series manufactured by Tosoh Corporation, SBN-70D, SBN-70P, MF-B60B, 17B-60P, TPA-B80E, and E402-B80B from the Duranate series manufactured by Asahi Kasei Corporation, and B-830, B-815N, B-820NSU, B-842N, B-846N, B870N, B874N, and B882N from the Takenate series manufactured by Mitsui Chemicals, Inc.
[0073] When the above composition C contains an isocyanate compound, the composition C preferably contains a non-silicone resin described below, and the non-silicone resin preferably has a curable group described below.
[0074] Carbodiimide compounds The carbodiimide compound can be synthesized by a conventional method. For example, a condensation reaction of a diisocyanate compound is used. The diisocyanate compound is not particularly limited, and may be any of an aromatic diisocyanate, an aliphatic diisocyanate, and an alicyclic diisocyanate.
[0075] Examples of aromatic diisocyanates include 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyl diisocyanate, tetraalkyldiphenylmethane diisocyanate, dialkyldiphenylmethane diisocyanate, 1,3-phenylene diisocyanate, polymeric diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-toluidine diisocyanate, 4,4'diphenyl ether diisocyanate, 1,5-naphthylene diisocyanate, and naphthalene diisocyanate.
[0076] Examples of aliphatic diisocyanates include hexamethylene diisocyanate, trimethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, xylylene diisocyanate, 1,2-propylene diisocyanate, butylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, and 1,5-pentamethylene diisocyanate.
[0077] Examples of alicyclic diisocyanates include 1,3-cyclopentane diisocyanate, 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, 2,4-methylcyclohexane diisocyanate, 2,6-methylcyclohexane diisocyanate, and norbornane diisocyanate.
[0078] The carbodiimide equivalent (the mass [g] of the carbodiimide compound required to provide 1 mole of carbodiimide groups) is preferably 100 to 1000 g / mol, more preferably 250 to 800 g / mol, and further preferably 300 to 700 g / mol.
[0079] When the above composition C contains a carbodiimide compound, the composition C preferably contains a non-silicone resin described below, and the non-silicone resin preferably has a curable group described below.
[0080] Melamine compounds In this specification, the melamine compound refers to melamine and a melamine derivative in which the hydrogen atom of the -NH2 group in melamine is replaced by a substituent. The melamine compound is not particularly limited, but may be a methylolmelamine compound obtained by condensing melamine with formaldehyde, in which one or more hydrogen atoms of the -NH2 group in the melamine are replaced with a methylol group (-CH2OH).In addition, the melamine compound may be an etherified methylolmelamine compound obtained by etherifying the above-mentioned methylolmelamine with an alcohol compound through dehydration condensation. Specifically, the melamine compound includes trimethylolmelamine, hexamethylolmelamine, trimethoxymethylmelamine, and hexamethoxymethylmelamine.
[0081] When the composition C contains a melamine compound, the composition C may not contain a non-silicone resin described later. When the composition C contains a melamine compound and does not contain a non-silicone resin described later, the composition C preferably contains an acid catalyst. As the acid catalyst, an organic acid catalyst is preferably used. As the organic acid catalyst, for example, an organic sulfonic acid such as p-toluenesulfonic acid, an organic carboxylic acid, etc. can be used.
[0082] Epoxy compounds The epoxy compound is not particularly limited as long as it is a compound having an epoxy group. The epoxy compound preferably has two or more epoxy groups in the molecule. The epoxy group in the epoxy compound may be an epoxy group contained in a glycidyl group, or an epoxy group contained in an alicyclic epoxy group. The alicyclic epoxy group refers to a group such as a 3,4-epoxycyclohexyl group. The epoxy compound may be a commercially available product. Examples of commercially available epoxy compounds include Cyclomer (registered trademark) M100, Celloxide (registered trademark) 2000, Celloxide (registered trademark) 2021P, 2081, Epolead (registered trademark) GT401, and EHPE (registered trademark) 3150 (manufactured by Daicel Corporation).
[0083] When the composition C contains an epoxy compound, the composition C may not contain a non-silicone resin described later. In this case, the composition C preferably contains a cationic polymerization initiator. The cationic polymerization initiator may be a photo-induced cationic polymerization initiator or a thermal cationic polymerization initiator. Furthermore, when the above composition C contains an epoxy compound, the composition C may contain a non-silicone resin described below, and when the composition C contains a non-silicone resin, it is preferable that the non-silicone resin has a curable group described below.
[0084] -Non-silicone resin- Examples of non-silicone resins include urethane resins, olefin resins, alkyd resins, acrylic resins, polyester resins, melamine resins, epoxy resins, phenolic resins, polyvinyl alcohol, and styrene-butadiene copolymers, and it is preferable to include a resin selected from the group consisting of acrylic resins, urethane resins, and olefin resins. The non-silicone resin preferably contains a curable group that crosslinks with a crosslinking agent. The curable group is preferably an acid group or a hydroxyl group. Examples of the acid group include a carboxy group, a sulfo group, a phosphonic acid group, and a phosphoric acid group, and the carboxy group is preferred. The acid group may also form an acid anhydride group. The acid group may also be in the form of a salt such as an alkali metal salt, an organic amine salt, or an ammonium salt.
[0085] Among these, the non-silicone resin is preferably at least one selected from the group consisting of hydroxyl group-containing acrylic resins, hydroxyl group-containing urethane resins, hydroxyl group-containing olefin resins, acid group-containing acrylic resins, acid group-containing urethane resins, and acid group-containing olefin resins, and is more preferably at least one selected from the group consisting of polyvinyl alcohol resins, acid group-containing acrylic resins, acid group-containing urethane resins, and acid group-containing olefin resins.
[0086] The urethane resin is not limited as long as it is a polymer having a urethane bond in the main chain, and known urethane resins such as reaction products of polyisocyanate compounds and polyol compounds can be used. The urethane resin can improve the solvent resistance of the release layer by adjusting the crosslinking reaction with the crosslinking agent, for example, by adjusting the structure and flexibility of each of the polyol compound and polyisocyanate compound that are raw materials. In order to improve the solvent resistance of the release layer, it is preferable that the urethane resin contains a polyester structure. Commercially available acid group-containing urethane resins include, for example, HYDRAN (registered trademark) AP-20, AP-40N, and AP-201 (all manufactured by DIC Corporation), TAKELAC (registered trademark) W-605, W-5030, and W-5920 (all manufactured by Mitsui Chemicals, Inc.), SUPERFLEX (registered trademark) 210 and 130, and ELASTRON (registered trademark) H-3-DF, E-37, and H-15 (all manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.).
[0087] The olefin resin may be any resin containing structural units derived from an olefin in the main chain. The olefin is not particularly limited, but is preferably an alkene having 2 to 6 carbon atoms, more preferably ethylene, propylene or hexene, and further preferably ethylene. The olefin-derived structural units contained in the olefin resin preferably account for 50 to 99 mol %, and more preferably 60 to 98 mol %, of all the structural units in the olefin resin.
[0088] Examples of the acid group-containing olefin resin include copolymers obtained by modifying the above-mentioned olefin resins with an acid-modifying component such as an unsaturated carboxylic acid or an anhydride thereof.
[0089] Commercially available acid group-containing olefin resins include, for example, the ZAIXXEN (registered trademark) series, such as ZAIXXEN AC, A, L, NC, and N (manufactured by Sumitomo Seika Chemicals Co., Ltd.), the CHEMIPEARL (registered trademark) series, such as CHEMIPEARL S100, S120, S200, S300, S650, and SA100 (manufactured by Mitsui Chemicals Co., Ltd.), and the HI-TECH (registered trademark) series, such as HI-TECH S3121 and S3148K (manufactured by Toho Chemicals Co., Ltd.). Examples of such an adhesive include Arrowbase (registered trademark) series, such as Arrowbase SE-1013, SE-1010, SB-1200, SD-1200, SD-1200, DA-1010, and DB-4010 (manufactured by Unitika Ltd.), Hardlen AP-2, NZ-1004, and NZ-1005 (manufactured by Toyobo Co., Ltd.), and Sepolsion G315 and VA407 (manufactured by Sumitomo Seika Chemicals Co., Ltd.). In addition, the acid-modified olefin resins described in paragraphs
[0022] to
[0034] of JP2014-076632A can also be preferably used.
[0090] The acrylic resin is a resin containing structural units derived from (meth)acrylate, and may contain structural units derived from a vinyl monomer such as styrene. The acrylic resin preferably contains a structural unit derived from a (meth)acrylate having an alkyl group with 1 to 12 carbon atoms, and more preferably contains a structural unit derived from a (meth)acrylate having an alkyl group with 1 to 8 carbon atoms. In order to suppress the precipitation of impurities such as oligomers contained in the polyester base material, the acid value of the acrylic resin is preferably 30 mgKOH / g or less, more preferably 20 mgKOH / g or less. The lower limit of the acid value is not particularly limited and is, for example, 0 mgKOH / g, but is preferably 2 mgKOH / g or more in terms of coating as an aqueous dispersion.
[0091] The polyvinyl alcohol resin is a resin containing a structural unit derived from vinyl alcohol in the main chain, and has a hydroxyl group. The polyvinyl alcohol resin may have a group other than the hydroxyl group (for example, a carboxy group). The polyvinyl alcohol resin may be copolymerized with vinyl alcohol, vinyl acetate, etc. Examples of monomers that may be copolymerized with vinyl alcohol include vinyl acetate and vinyl butyral. The polyvinyl alcohol resin may be partially saponified or completely saponified. Specifically, the saponification degree of the polyvinyl alcohol resin is preferably 80 to 100, and more preferably 90 to 100.
[0092] The content of the silicone chain-free cured material in the release layer is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass or more, based on the total mass of the release layer. The content of the silicone chain-free cured material in the release layer is preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less, based on the total mass of the release layer, in order to reduce the peeling speed dependency of the peeling force.
[0093] (Additives) The release layer may contain components other than the silicone chain-containing cured product and the silicone chain-free cured product. For example, the release layer may contain components that may be contained in the above-mentioned composition A and components derived from that component, and components that may be contained in the composition C and components derived from that component. The release layer may contain additives other than the above components, such as a light release additive and a heavy release additive for adjusting the release force, an adhesion improver, and an antistatic agent.
[0094] The release layer may be provided directly on the surface of the polyester substrate or via an intermediate layer, but it is preferable to provide the release layer directly on the surface of the polyester substrate from the viewpoint of superior productivity. In other words, it is preferable that the polyester substrate and the release layer are adjacent to each other.
[0095] (Characteristics of the peeling layer, etc.) The characteristics of the release layer will be described below.
[0096] -Distribution of silicone chain-containing cured material in the release layer- In the release layer, the arrangement of the silicone chain-containing cured material and the silicone chain-free cured material is not particularly limited. In particular, it is preferable that the silicone chain-containing cured material is contained in a large amount on the surface side (release surface side) of the release layer. That is, it is preferable that the silicone chain-containing cured material is segregated on the release surface side in the release layer. The distribution of the silicone chain-containing cured material content in the release layer can be confirmed, for example, by secondary ion mass spectrometry (SIMS). More specifically, a method can be used in which the surface of the release layer is cut and fragment ions derived from silicone chains on the surface of the release layer are analyzed by SIMS.
[0097] In addition, whether or not the silicone chain-containing cured material segregates to the peeled surface side can be determined by the surface free energy (E Si ) and the surface free energy (E P ) and the surface free energy (E R ) to check. For example, E R E P E than Si When the surface free energy is close to 0.05, it can be determined that the silicone chain-containing cured product is segregated on the release surface side. The surface free energy can be measured by the method described below.
[0098] -Thickness of peeling layer- The thickness of the release layer is preferably 200 nm or less, more preferably 100 nm or less, more preferably 65 nm or less, particularly preferably 50 nm or less, and most preferably 40 nm or less, in that the peeling force has a lower peeling speed dependency, and is preferably 2 nm or more, more preferably 10 nm or more. The thickness of the release layer is defined as the arithmetic average value of the thicknesses of five points of the resin layer in a slice prepared by preparing a slice having a cross section perpendicular to the main surface of the polyester film and measuring the thickness using a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0099] -Logarithmic Decay Rate- The logarithmic decrement of the release layer is preferably 0.10 or less, more preferably 0.06 or less, and even more preferably 0.05 or less. There is no particular lower limit to the logarithmic decrement, but it may be, for example, 0.001 or more. The logarithmic decrement of the release layer is measured by performing a pendulum viscoelasticity test at 25° C. Specifically, a rigid pendulum viscoelasticity tester (RPT-3000W) manufactured by A&D Corporation is used to measure the decrement by placing a polyester film sample so that the cylinder edge is in contact with the release layer side.
[0100] -Surface free energy- The surface free energy of the release layer (the surface opposite to the polyester substrate) is 50 mJ / m 2 In most cases, the peel force is less dependent on the peel rate, so it is usually less than 30 mJ / m 2 Less than 25 mJ / m is preferable. 2 The surface free energy of the release layer on the release surface is preferably 16 mJ / m 2 In many cases, it is more than that. The surface free energy of the release surface of the release layer can be measured by the following method. Using a contact angle meter (Kyowa Interface Science, DROPMASTER-501), a droplet is placed on the release surface of this film at 25°C, and the contact angle is measured 1 second after the droplet adheres to the surface. 2μL of purified water, 1μL of methylene iodide, and 1μL of ethylene glycol are used as droplets, and the surface free energy is calculated from the measured contact angles using the Kitazaki-Hata method.
[0101] -Maximum protrusion height and average surface roughness- The maximum protrusion height (Sp) of the release surface of the release layer is preferably 30 nm or less, and is often 1 nm or more. The surface average roughness (Sa) of the release surface of the release layer is preferably from 0 to 10 nm, and more preferably from 0 to 5 nm. The maximum protrusion height and average surface roughness of the release surface of the release layer can be adjusted by selecting the type of polyester and additives constituting the polyester base material so that the polyester base material is substantially free of particles and forms a smooth film (e.g., by using a polyester resin polymerized using a titanium compound or an aluminum compound, etc.). The maximum protrusion height and average surface roughness of the release layer surface of a polyester film are determined by measuring the release surface of the release layer of the polyester film using an optical interferometer (e.g., "Vertscan 3300G Lite" manufactured by Hitachi High-Tech Corporation) under the following conditions, and then analyzing the results using the built-in data analysis software. When measuring the maximum projection height, the measurement position is changed and measurements are taken five times, with the maximum value of the measured values being taken as the measured maximum projection height (represented as P in the built-in data analysis software). When measuring the average surface roughness, the measurement position is changed and measurements are taken five times, with the average value of the measured values being taken as the measured surface roughness.
[0102] In addition, whether or not the silicone compound in the release layer of this film is a silicone chain-containing cured product can be evaluated by the migration of the silicone compound. Specifically, when an adhesive tape is attached to the release layer and then peeled off, if there is a certain level of change in the peeling force of the adhesive tape, it is determined that the silicone compound has migrated. In the release layer of this film, the silicone compound is a silicone chain-containing cured product, so the silicone is less likely to migrate. Specifically, the residual adhesion rate evaluated in the examples section below is preferably 75% or more, and more preferably 85% or more.
[0103] <Protrusions and protrusion-containing layer> The present film preferably has protrusions on the surface of the polyester film on the polyester substrate side (the surface of the polyester film opposite to the release surface, hereinafter also referred to as the "smooth surface"). When the present film has protrusions on the smooth surface, the polyester film has excellent slip properties and can be improved in transportability.
[0104] The height of the protrusions is preferably 0.02 μm or more, more preferably 0.03 μm or more, from the viewpoint of excellent transportability. The height of the protrusions is preferably 1.0 μm or less, more preferably 0.6 μm or less, even more preferably 0.1 μm or less, and particularly preferably less than 0.06 μm. If the height of the protrusions is within the above range, it is easy to control the dynamic friction coefficient to 0.2 or more when the release surface of the present film is brought into contact with the easy-to-slip surface, and winding failures such as winding slippage are less likely to occur when the present film is wound up.
[0105] The above-mentioned protrusions may be formed directly on the above-mentioned polyester substrate, or may be formed by a protrusion-containing layer that is a layer separate from the polyester substrate. That is, the present film may have a protrusion-containing layer on the side opposite to the release layer side of the polyester substrate. In other words, the present film may have a release layer, a polyester substrate, and a protrusion-containing layer in this order. The protrusion-containing layer refers to a layer having protrusions on at least one surface thereof. The protrusion-containing layer may be provided directly on the surface of the polyester substrate or via an intermediate layer, but it is preferable to provide it directly on the surface of the polyester substrate from the viewpoint of superior productivity. That is, the present film may be composed of a release layer, a polyester substrate, and a protrusion-containing layer, and the release layer and the polyester substrate may be adjacent to each other, and the polyester substrate and the protrusion-containing layer may be adjacent to each other.
[0106] The method of forming the protrusion-containing layer is not particularly limited as long as protrusions are formed on at least one surface of the protrusion-containing layer. For example, a method of providing a layer containing particles (hereinafter also referred to as a "particle-containing layer") as the protrusion-containing layer on the surface opposite to the release surface of the polyester substrate can be mentioned. Hereinafter, a particle-containing layer will be described as an example of the protrusion-containing layer.
[0107] (Particle-containing layer) The particle-containing layer is not particularly limited as long as it contains particles. The particle-containing layer preferably contains a binder in addition to the particles. The particle-containing layer may further contain an additive.
[0108] The average particle size of the particles contained in the particle-containing layer is not particularly limited, but is preferably from 1 to 1000 nm, and more preferably from 40 to 500 nm. The particles include inorganic particles and organic particles. Examples of inorganic particles include silica particles (silicon dioxide particles, colloidal silica), titania particles (titanium oxide particles), calcium carbonate, barium sulfate, and alumina particles (aluminum oxide particles). Examples of organic particles include resin particles. Examples of resins constituting resin particles include acrylic resins such as polymethylmethacrylate resin (PMMA), polyester resins, silicone resins, styrene resins, urethane resins, and styrene-acrylic resins. Resin particles may or may not have a crosslinked structure. Specific examples include non-crosslinked acrylic resin particles, non-crosslinked styrene resin particles, crosslinked acrylic resin particles, crosslinked urethane resin particles, and divinylbenzene crosslinked particles. In this specification, acrylic resin means a resin containing a structural unit derived from acrylate or methacrylate.
[0109] The content of the particles in the particle-containing layer is preferably from 0.1 to 30% by mass, and more preferably from 1 to 25% by mass, based on the total mass of the particle-containing layer, from the viewpoint of transportability.
[0110] By adjusting the type, particle size and content of the particles in the particle-containing layer, the dynamic friction coefficient between the release surface and the slippery surface (the surface of the particle-containing layer opposite the polyester substrate) can be adjusted.
[0111] The binder that the particle-containing layer may contain is preferably a resin binder. Examples of the resin binder include acrylic resin, urethane resin, polyester resin, and olefin resin. Non-polyester resin is preferable, and specifically, acrylic resin, urethane resin, or olefin resin is preferable. Known resins can be used as the binder. The resin binder may also be an acid-modified resin. The binder contained in the particle-containing layer may have a crosslinked structure, that is, the particle-containing layer may be a crosslinked film. The particle-containing layer may contain a single type of binder, or may contain two or more types of binders. The content of the binder is preferably from 30 to 99.8% by mass, and more preferably from 50 to 99.5% by mass, based on the total mass of the particle-containing layer.
[0112] Examples of additives contained in the particle-containing layer include surfactants, waxes, antioxidants, ultraviolet absorbers, colorants, reinforcing agents, plasticizers, antistatic agents, flame retardants, rust inhibitors, and fungicides.
[0113] The particle-containing layer preferably contains a surfactant in order to improve the smoothness of the surface. The surfactant is not particularly limited, and examples thereof include silicone-based surfactants, fluorine-based surfactants, and hydrocarbon-based surfactants. Of these, fluorine-based surfactants (particularly, fluorine-based surfactants having a perfluoroalkyl group having 1 to 4 carbon atoms) or hydrocarbon-based surfactants are preferred. The surfactant may be used alone or in combination of two or more kinds. The content of the surfactant is preferably 0.1 to 10% by mass, and more preferably 0.1 to 5% by mass, based on the total mass of the particle-containing layer, in terms of superior surface smoothness.
[0114] The thickness of the particle-containing layer is preferably from 1 nm to 1 μm, more preferably from 1 to 500 nm, and even more preferably from 1 to 200 nm, in order to achieve low haze. The thickness of the particle-containing layer is defined as the arithmetic average value of the thicknesses of the particle-containing layer at five points in a slice prepared by cutting the polyester film in a cross section perpendicular to the main surface of the polyester film and measuring the thicknesses using a scanning electron microscope (SEM).
[0115] The maximum projection height (Sp) of the protrusion-containing layer is preferably 30 nm or more. The maximum projection height of the protrusion-containing layer is preferably 300 nm or less. The maximum projection height of the protrusion-containing layer can be measured in the same manner as the maximum projection height of the release layer.
[0116] <Characteristics of polyester film> The polyester film preferably exhibits various characteristics. The preferable characteristics of the polyester film will be described below.
[0117] The thickness of the polyester film is preferably 200 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, particularly preferably 40 μm or less, and most preferably 35 μm or less, from the viewpoint of excellent cost efficiency. The lower limit of the thickness is not particularly limited, but is preferably 1 μm or more, more preferably 3 μm or more, even more preferably 10 μm or more, particularly preferably 18 μm or more, and most preferably 20 μm or more, from the viewpoint of improved strength and improved processability. The thickness of the polyester film is measured at five different randomly selected points using a stylus film thickness meter, and the arithmetic mean value of the measured values is taken as the thickness.
[0118] In the present film, the dynamic friction coefficient is preferably 0.2 or more. The dynamic friction coefficient in the present film refers to the friction coefficient on both sides of the present film, more specifically, the dynamic friction coefficient between the surface of the release layer (release surface) and the surface of the present film opposite the release surface (slippery surface, for example, the surface opposite the polyester substrate side of the protrusion-containing layer). If the dynamic friction coefficient is 0.2 or more, the present film is less likely to slip when wound into a roll. The dynamic friction coefficient is preferably less than 1.0, which makes it difficult for blocking to occur when the present film is wound into a roll. The dynamic friction coefficient can be measured in accordance with ASTM D 1894-95. The detailed procedure for measuring the dynamic friction coefficient is as described in the examples below.
[0119] [Manufacturing method of polyester film] The method for producing a polyester film of the present invention is a method for producing a polyester film comprising a release layer and a polyester substrate, and includes a step of applying a composition containing a component that forms a silicone chain-containing cured product and a component that forms a silicone chain-free cured product (hereinafter also referred to as "composition M") to one surface of the polyester substrate. According to the method for producing a polyester film of the present invention, the above-mentioned polyester film of the present invention can be produced. Hereinafter, the method for producing a polyester film of the present invention is also referred to as "the method for producing the present film".
[0120] The method for producing the film of the present invention may include other steps than those described above, such as a method in which a polyester resin is melt-extruded to produce an unstretched polyester substrate, the unstretched polyester substrate is stretched longitudinally, the composition M is applied to one side of the longitudinally stretched polyester substrate, and the resulting polyester substrate is then stretched transversely to produce a polyester film. In other words, one embodiment of the method for producing the present film includes a longitudinal stretching step of longitudinally stretching an unstretched polyester substrate, a layer formation step of forming a release layer, and a transverse stretching step of transversely stretching the polyester substrate. One embodiment of the method for producing the present film will now be described.
[0121] The method for producing the present film preferably includes the longitudinal stretching step. The longitudinal stretching can be carried out, for example, by conveying the unstretched polyester base material in the machine direction while applying tension between two or more pairs of stretching rolls disposed in the conveying direction. The stretching ratio in the longitudinal stretching step is appropriately set depending on the application, but is preferably 2.0 to 5.0 times, more preferably 2.5 to 4.0 times, and even more preferably 2.8 to 4.0 times.
[0122] The present film manufacturing method preferably includes a layer-forming step. Hereinafter, an embodiment will be described in which the layer-forming step includes a step of applying a composition (composition M) containing a component that forms a silicone chain-containing cured product and a component that forms a silicone chain-free cured product to one side of a polyester substrate.
[0123] Composition M contains a component that forms a silicone chain-containing cured product, and a component that forms a silicone chain-free cured product. The components forming the silicone chain-containing cured product include the first compound and the second compound described above. That is, the composition M preferably contains the first compound and the second compound described above. The composition M also preferably contains a curing catalyst that promotes the reaction of the first compound and the second compound. The curing catalyst is also as described above. The composition M may also contain a surfactant. When the composition M contains the first compound and the second compound as components forming the silicone chain-containing cured product, the ratio of the content of the second compound to the content of the first compound is not particularly limited. In particular, the ratio of the number of moles of SiH groups contained in the second compound to the total number of moles of alkenyl groups contained in the first compound is preferably adjusted to 1.0 to 5.0, more preferably adjusted to 2.0 to 4.0.
[0124] The component that forms the silicone chain-free cured product includes the above-mentioned crosslinking agent and the combination of the above-mentioned crosslinking agent and non-silicone resin.That is, it is preferable that composition M contains the above-mentioned crosslinking agent or the above-mentioned crosslinking agent and non-silicone resin.Note that, when composition M contains only crosslinking agent as the component that forms the silicone chain-free cured product, it is preferable that composition M contains the above-mentioned acid catalyst or cationic polymerization initiator. When composition M contains a crosslinking agent and a non-silicone resin as components that form a silicone chain-free cured product, the ratio of the content of the non-silicone resin to the content of the crosslinking agent is not particularly limited. In particular, the ratio is preferably 0.1 to 20.0, more preferably 0.2 to 16.0, and even more preferably 0.3 to 2.0.
[0125] Composition M preferably contains a solvent in addition to the components that form a silicone chain-containing cured product, the components that form a silicone chain-free cured product, and the above-mentioned components. Solvents include water and organic solvents.
[0126] The contents of the components that form a silicone chain-containing cured product and the components that form a silicone chain-free cured product in composition M can be adjusted so as to obtain the preferred contents of the silicone chain-containing cured product and the silicone chain-free cured product in the release layer described above.
[0127] Composition M may be prepared by mixing composition A and composition C described above.
[0128] There is no particular limitation on the method for applying the composition M, and any known method can be used. Examples of the application method include spray coating, slit coating, roll coating, blade coating, spin coating, bar coating, and dip coating. As a coating method, it is preferable to use an in-line coating method in which composition M is applied to one surface of the longitudinally stretched polyester substrate while the longitudinally stretched polyester substrate is being transported.
[0129] In addition, when producing a polyester film having a protrusion-containing layer, for example, a composition for forming a particle-containing layer may be applied to the surface of the polyester base opposite to the surface coated with composition M. The composition for forming a particle-containing layer may be any composition containing the components contained in the particle-containing layer described above.
[0130] The present film production method preferably includes the above-mentioned transverse stretching step. Transverse stretching refers to a treatment of stretching the polyester base material in the width direction.
[0131] The present film manufacturing method may include other steps in addition to the above-mentioned longitudinal stretching step, the above-mentioned layer forming step, and the above-mentioned transverse stretching step. The manufacturing method according to the present embodiment may include, for example, one or more steps selected from the group consisting of a heat setting step of heating and heat setting a biaxially stretched polyester base material, a heat relaxing step of heating the polyester base material heat-set in the heat setting step at a temperature lower than that in the heat setting step to heat relax the polyester base material heat-relaxed in the heat relaxing step, a cooling step of cooling the polyester base material heat-relaxed in the heat relaxing step, and an expansion step of expanding the heat-relaxed polyester base material in the width direction during the cooling step.
[0132] In the above, the polyester film is produced by applying the composition M to one surface of the polyester substrate between the longitudinal stretching step and the transverse stretching step, but the film production method is not limited to the above method. For example, the composition M may be applied to one surface of the polyester substrate after the transverse stretching step.
[0133] [Application] The film can be used in a variety of applications. For example, the present film is preferably used as a release film (carrier film) for producing a ceramic green sheet. The ceramic green sheet produced using the present film can be suitably used for producing ceramic capacitors, which require multi-layered internal electrodes in order to meet the demands of miniaturization and large capacity.
[0134] The method for producing a ceramic green sheet using the present film is not particularly limited and can be carried out by a known method. For example, the method for producing a ceramic green sheet includes a method of applying a prepared ceramic slurry to the release layer surface of the present film and drying and removing the solvent contained in the ceramic slurry. The method of applying the ceramic slurry is not particularly limited, and for example, a known method such as a method of applying a ceramic slurry formed by dispersing ceramic powder and a binder in a solvent by a reverse roll method and removing the solvent by heating and drying can be applied. The binder is not particularly limited, and examples thereof include polyvinyl butyral. The solvent is also not particularly limited, and examples thereof include ethanol and toluene.
[0135] The produced ceramic green sheet is used to produce a ceramic capacitor. As a method for producing a ceramic capacitor using the ceramic green sheet, a known method can be applied, for example, the following method. First, internal electrodes are provided on a laminate of the present film and ceramic green sheets by coating or printing a conductive paste. Next, the present film is removed from the laminate, and ceramic green sheets with internal electrodes are stacked in order, and the resulting laminate is pressed to produce an intermediate laminate. After cutting the intermediate laminate into a desired shape, the cut intermediate laminate is fired to obtain a ceramic body. Next, external electrodes that are electrically connected to the internal electrodes are formed on each of the two end faces of the fired intermediate laminate using a conductive paste such as silver, thereby obtaining a ceramic capacitor.
[0136] This film can also be used as a protective film for dry film resists, a film for sheet molding such as decorative layers and resin sheets, a release film for process manufacturing such as in the semiconductor manufacturing process, a release film for the polarizing plate manufacturing process, and a separator for adhesive films for labels, medical and office supplies, etc. EXAMPLES
[0137] The present invention will be described in further detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.
[0138] [Production of polyester film] <Example 1> The unstretched polyester substrate obtained was longitudinally stretched with reference to the conditions described in
[0160] to
[0169] of WO 2020 / 158316. The following protrusion-containing layer forming composition X1 was applied to one side of the longitudinally stretched polyester substrate, and the following composition L1 was applied to the other side. Each of the formed coating films was dried with hot air at 100 ° C. to form a protrusion-containing layer and a release layer. That is, the protrusion-containing layer forming composition X1 and the composition L1 were in-line coated. At this time, the coating amounts of the protrusion-containing layer forming composition X1 and the composition L1 were adjusted so that the thickness of the formed protrusion-containing layer was 60 nm and the thickness of the formed release layer was 15 nm. The obtained film with the coating layer was stretched laterally to produce a biaxially stretched polyester film, which was then wound into a roll of 7000 m. No knurling process was performed. The thickness of the polyester film of Example 1 produced (including the thickness of the protrusion-containing layer and the release layer) was 31 μm. The thickness of the protrusion-containing layer was 60 nm. The thickness of the release layer was as shown in the table below.
[0139] (Protrusion-containing layer forming composition X1) The components shown below were mixed to prepare a protrusion-containing layer-forming composition X1. The prepared composition X was subjected to filtration using a depth-pleated type filter (SHPH010, manufactured by ROKI TECHNO CORPORATION) with a pore size of 1 μm, and membrane degassing (2x6 Radial Flow Superphobic, manufactured by Polypore Corporation). Acid-modified polyolefin (Zaixen (registered trademark) NC, manufactured by Sumitomo Seika Chemicals Co., Ltd., an aqueous dispersion prepared by adding water to a solid content of 25% by mass): 157 parts Anionic hydrocarbon surfactant (Rapisol (registered trademark) A-90, sodium di-2-ethylhexyl sulfosuccinate, manufactured by NOF Corporation, solid content 1% by mass diluted with water): 56 parts Particles (Snowtex (registered trademark) ZL, manufactured by Nissan Chemical Industries, Ltd., colloidal silica, solid content 40% by mass, aqueous dispersion): 11 parts ·Wed: 776 copies
[0140] (Composition L1) Composition L1 was prepared by mixing composition A1, composition C1, and other additives according to the procedure described below. The prepared composition L1 was subjected to filtration using a filter with a pore size of 6 μm (F20, manufactured by Mahle Filter Systems Co., Ltd.) and membrane degassing (2x6 Radial Flow Superphobic, manufactured by Polypore Co., Ltd.). The composition L1 corresponds to the composition M described above.
[0141] -Composition A1- Composition A1 was obtained by mixing emulsion (I) and emulsion (II) obtained by the procedure described below. First, (A) 50 parts by mass of vinyl-containing polydimethylsiloxane with both ends blocked with dimethylvinylsilyl groups, (B) 0.5 parts by mass of platinum-vinylsiloxane complex solution with a platinum content of 1% by mass, (C) 0.11 parts by mass of 1-ethynyl-1-cyclohexanol (manufactured by Nissin Chemical Industry Co., Ltd.), (D) 6.6 parts by mass of nonionic surfactant (Naroacty CL-95 manufactured by Sanyo Chemical Industries Co., Ltd.), and (E) 44 parts by mass of purified water were mixed and stirred to prepare emulsion (I). The platinum content was 100 ppm by mass relative to the mass of polydimethylsiloxane (A). Furthermore, 35 parts by mass of (F) methylhydrogenpolysiloxane having SiH groups on the side chains and both molecular chain terminals blocked with trimethylsiloxy groups, 5 parts by mass of (G) a nonionic surfactant (Naroacty CL-95, manufactured by Sanyo Chemical Industries, Ltd.), and 60 parts by mass of (H) purified water were mixed and stirred to prepare emulsion (II). Next, emulsion (I) and emulsion (II) were mixed and further diluted with purified water so that the solid content concentration became 40 mass % to prepare composition A1. The mixing ratio of emulsion (I) and emulsion (II) was adjusted so that the ratio of the total number of moles of SiH groups in component (F) to the total number of moles of alkenyl groups in component (A) was 2.9.
[0142] -Composition C1- The following components were mixed to obtain composition C1. Aqueous dispersion of acrylic resin Z1 (acrylic resin copolymerized with a composition of methyl methacrylate / styrene / 2-ethylhexyl acrylate / 2-hydroxyethyl methacrylate / acrylic acid = 59:8:23:5:5 (mass ratio)) (solid concentration 20 mass%, acid value 69 mmol / g): 140 mass parts Oxazoline crosslinking agent (aqueous solution containing an oxazoline compound, EPOCROS (registered trademark) WS-700, manufactured by Nippon Shokubai Co., Ltd., aqueous solution with a solid content of 25% by mass): 112 parts by mass ·Water: 1316 parts by mass
[0143] -Other additives- Composition T was prepared by mixing the following components. Silane coupling agent (KBE-403, manufactured by Shin-Etsu Chemical Co., Ltd.): 5 parts by weight Nonionic surfactant (Naroacty CL-95, manufactured by Sanyo Chemical Industries): 2 parts by weight
[0144] Composition L1 was prepared by mixing compositions A1, C1, and T in such an adjusted ratio that the solid content of composition A1, the solid content of each component of composition C1 (acrylic resin Z1 and oxazoline crosslinking agent), and the solid content of composition T were the values shown in the table below.
[0145] <Examples 2 to 12> The polyester films of Examples 2 to 12 were obtained in the same manner as in Example 1, except that compositions L2 to L10, in which the components and amounts were changed as shown in the table below, were used instead of composition L1. However, in Example 9, composition X2 for forming a protrusion-containing layer was used instead of composition X1 for forming a protrusion-containing layer. The amount of each component in compositions L2 to L10 was adjusted so that the solid content of each component was the same as that of composition L1. Details of the components contained in compositions L2 to L10 and described in the table are shown below.
[0146] Urethane resin Z2: Aqueous dispersion of urethane resin having carboxy groups obtained by synthesizing with a composition of isophorone diisocyanate / terephthalic acid / isophthalic acid / ethylene glycol / diethylene glycol / dimethylolpropanoic acid = 12 / 19 / 18 / 21 / 25 / 5 (mol%) Epoxy crosslinker: Denacol EX-521 Carbodiimide crosslinking agent: Aqueous solution containing a carbodiimide compound (Carbodilite V-02-L2, manufactured by Nisshinbo Chemical Co., Ltd., aqueous solution with 25% solids by mass) Isocyanate crosslinking agent: a solution containing a blocked isocyanate compound (Duranate (registered trademark) WM44-L70G, manufactured by Asahi Kasei Corporation, a dipropylene glycol dimethyl ether solution with a solid content of 70% by mass)
[0147] Protrusion-containing layer forming composition X2 was obtained in the same manner as for protrusion-containing layer forming composition X1, except that the following components were contained. Aqueous dispersion of urethane resin (Superflex (registered trademark) 210, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) with a solid content concentration of 35% by mass: 115 parts by mass Anionic hydrocarbon surfactant (Rapisol (registered trademark) A-90, manufactured by NOF Corporation) with a solid content concentration of 1% by mass diluted with water: 36 parts by mass Aqueous dispersion of non-crosslinked styrene resin particles (Nipol (registered trademark) UFN1008, manufactured by Zeon Corporation) with a solid content of 20% by mass: 11.2 parts by mass Particles (PMMA resin particles, MP1000, manufactured by Soken Chemical & Engineering Co., Ltd.) solids concentration 5% by mass aqueous dispersion: 179.2 parts by mass Crosslinking agent (oxazoline compound, EPOCROS (registered trademark) WS-700, manufactured by Nippon Shokubai Co., Ltd.) aqueous solution with a solid content of 25% by mass: 32.2 parts by mass ·Water: 622 parts by mass
[0148] <Comparative Example 1> Except for using the following composition LX1 instead of composition L1, a polyester film of Comparative Example 1 was obtained in the same manner as in Example 1. Note that the polyester film of Comparative Example 1 did not contain a silicone chain-free cured material in the release layer.
[0149] (Composition LX1) Composition LX1 was prepared with reference to Example 14 of Patent Document 1 mentioned above. Specifically, the silicone compound S1 is a silicone compound S1 corresponding to silicone A-14 (containing a dimethylsiloxane unit and a Q unit (SiO 4 / 2 A compound corresponding to a silicone compound containing a unit represented by the following formula was obtained. The content of Q units in the silicone compound S1 was 40.60 mol % based on all units. Furthermore, as the silicone compound S2, a compound corresponding to Silicone A-19 (organopolysiloxane compound having an alkenyl group, siloxane unit having an alkenyl group: 10 mol %) was obtained. Furthermore, as the silicone compound S3, a compound corresponding to the silicone compound B (organohydrogenpolysiloxane containing a SiH group, number average molecular weight: 4500) was obtained. The repeat number of the unit having a SiH group was adjusted to 30. Silicone compound S1, silicone compound S2, and silicone compound S3 were each prepared as an emulsion with water containing a surfactant, with S1 and S2 having a solid content of 20% by mass, and S3 having a solid content of 10% by mass. The emulsions of the silicone compound S1, silicone compound S2, and silicone compound S3 were mixed to be 50 parts by mass, 50 parts by mass, and 3.0 parts by mass, respectively, and then 0.02 parts by mass of a platinum catalyst was added and diluted with water. A crosslinking reaction inhibitor was added in an amount of 150 ppm (parts per million) relative to the mass of the liquid obtained by dilution with water, to obtain a composition LX1. The platinum catalyst used was a platinum catalyst emulsion (manufactured by Shin-Etsu Chemical Co., Ltd., product name "CATPM-10A"), and the crosslinking reaction inhibitor used was 1-ethynylcyclohexanol (manufactured by Lancaster).
[0150] The dilution with water when obtaining composition LX1 was adjusted so that the coating thickness would be the value shown in the table below.
[0151] <Comparative Example 2> Except for using the following composition LX2 instead of composition L1, a polyester film of Comparative Example 1 was obtained in the same manner as in Example 1. Note that the polyester film of Comparative Example 2 did not contain a silicone chain-containing cured product in the release layer.
[0152] (Composition LX2) Composition LX2 was prepared by obtaining acrylic resin ZX2 and oxazoline-based crosslinking agent OX2 in the following manner so as to have the contents shown in the following paragraph.
[0153] -Manufacture of acrylic resin ZX2- In a four-neck flask equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen inlet tube, 100 parts by mass of hydroxyethyl methacrylate (HEMA), 8 parts by mass of methacrylic acid (MAA), 33 parts by mass of stearyl methacrylate (SMA), 3 parts by mass of methyl methacrylate (MMA), and 336 parts by mass of isopropyl alcohol (IPA) were placed, and the temperature in the flask was raised to 80°C while stirring. Stirring was performed for 3 hours while maintaining the temperature in the flask at 80°C. After stirring, 0.5 parts by mass of 2,2-azobis-2-methyl-N-2-hydroxyethylpropionamide was added to the flask. Thereafter, nitrogen replacement was performed while heating the flask to 120°C, and the mixture was stirred at 120°C for 2 hours to obtain a mixture of acrylic resin and solvent. Next, the flask was decompressed to 1.5 kPa while keeping the flask at 120°C, and the unreacted raw materials and the solvent were removed. After removing the solvent, the flask was returned to atmospheric pressure and cooled to room temperature, and 575 parts by mass of an aqueous IPA solution (water content 50% by mass) was added and stirred. Then, while stirring, an aqueous ammonia solution was added using a dropping funnel, and the acrylic resin was neutralized until the pH of the solution was in the range of 5.5 to 7.5, and an acrylic resin (acrylic resin ZX2) with a solid content concentration of 20% by mass was obtained.
[0154] -Production of oxazoline crosslinking agent OX2- A flask equipped with a stirrer, reflux condenser, nitrogen inlet tube and thermometer was charged with 460.6 parts of IPA, and heated to 80°C while gently flowing nitrogen gas. A monomer mixture consisting of 126 parts of methyl methacrylate, 210 parts of 2-isopropenyl-2-oxazoline and 84 parts of methoxypolyethylene glycol acrylate, which had been prepared in advance, and an initiator solution consisting of 21 parts of 2,2'-azobis(2-methylbutyronitrile) ("ABN-E" manufactured by Nippon Hydrazine Kogyo Co., Ltd.) and 189 parts of isopropyl alcohol were each dripped into the flask over a period of 2 hours from the drip funnel to react with each other. After the dripping was completed, the reaction was continued for 5 hours to obtain a reaction liquid. Nitrogen gas was continued to flow during the reaction, and the temperature inside the flask was maintained at 80±1°C. The reaction liquid was then cooled to obtain a resin having an oxazoline group with a solid content concentration of 10% (oxazoline-based crosslinking agent OX2).
[0155] Composition LX2 was prepared by mixing the following components in the following amounts: ·Water: 45.76 parts by mass Isopropyl alcohol: 28.20 parts by weight Acrylic resin ZX2 (solid content concentration 20% by mass): 14.00 parts by mass Oxazoline-based crosslinking agent OX2 (solid content concentration 10% by mass): 12.00 parts by mass Additive T2 (polyether modified polydimethylsiloxane, 67Additive, solids concentration 100% by mass, manufactured by Dow Corning Toray Co., Ltd.): 0.04 parts by mass
[0156] [measurement] <Surface free energy> Using the method described above, the surface free energy of the peeled surface (unit: mJ / m 2 The results are shown in the table below.
[0157] <Logarithmic decrement rate> The logarithmic decrement of the release layer was measured using the method described above, and the results are shown in the table below.
[0158] <Measurement of static and dynamic friction coefficients> The static and dynamic friction coefficients between the release surface of the obtained polyester film and a slippery surface were measured in accordance with ASTM D 1894-95 under the following conditions. As a measurement condition, the distance that the flat indenter was moved in the length direction of the fixed test piece was set to 130 mm. The force required to move the flat indenter (test force) was recorded by a measuring device, and a plot was created with the moving distance (unit: mm) on the horizontal axis and the test force (unit: N) on the vertical axis. The static friction coefficient and the kinetic friction coefficient were calculated from the measured values of the test forces plotted above. The above procedure was repeated five times, and the averages of the dynamic friction coefficient and static friction coefficient were calculated. In the table below, the average dynamic friction coefficient is shown as the dynamic friction coefficient, and the average static friction coefficient is shown as the static friction coefficient.
[0159] [evaluation] <Peeling speed dependence> The peel rate dependency of each polyester film was evaluated according to the following procedure. A polyester film sample was cut out, a 25 mm wide Nitto Denko 31B adhesive tape (polyester adhesive tape) was attached to the release surface, and a pressure roller was applied once back and forth. The tape-attached sample was then cut into a width of 25 mm and a length of 100 mm, and stored at room temperature for 24 hours. After 24 hours of storage, the 3B adhesive tape side of the sample was attached and fixed to an aluminum plate, and the aluminum plate was fixed to a tensile tester. In this state, the end of the polyester film was pulled at an angle of 180°. The pulling speed (peeling speed) was set to 0.3 m / min and 10 m / min, and the peeling force was measured for each. This measurement was performed three times, and the average value was taken as the peeling force (unit: mN / 25 mm) at each peeling speed.
[0160] From the peel force at 0.3 m / min and the peel force at 10 m / min, an index of peel rate dependency (Ds) represented by the following formula (D1) was calculated, and the peel rate dependency was evaluated from the Ds value based on the following evaluation criteria. The peel rate dependency was preferably rated A or B, and more preferably A. When peeling did not occur in the above test and the peel force could not be measured, it was rated D. Formula (D1) Ds = (peel force at 10 m / min) / (peel force at 0.3 m / min) A:Ds≦1.5 B: 1.5 <Ds≦2.0 C:2.0 <Ds D: Peeling was not possible and the peeling force could not be measured.
[0161] <Transferability> The residual adhesion rate, which is represented by the formula described below, was calculated according to the following procedure, and the migration of the components contained in the release layer was evaluated. First, a polyester adhesive tape (Nitto Denko Corporation, No. 31B) was attached to a polyester substrate on which no release layer was formed, and the peel strength was measured and taken as the standard adhesive strength (f0). Also, a polyester adhesive tape was pressed onto the release surface of the polyester film with a 5 kg rubber roller, and after maintaining this for 30 seconds, the polyester adhesive tape was peeled off. Next, the polyester adhesive tape peeled off from the release surface was attached to a polyester substrate on which no release layer was formed, and the peel strength was measured in the same manner as for f0, and was taken as the residual adhesive strength (f). From the obtained standard adhesive strength (f0) and the residual adhesive strength (f), the residual adhesive rate (unit: %) represented by the following formula (F1) was calculated. Note that the peel angle in measuring the peel strength was 180° in all cases, and the peel speed was 300 mm / min. Formula (F1) (residual adhesion rate)={f / f0}×100
[0162] Based on the obtained residual adhesion rate value, the migration was evaluated according to the following criteria. The migration rate is preferably rated A or B, and more preferably A. If the hardening property of the release layer is low, the components of the release layer are likely to migrate to the pressure-sensitive adhesive tape, and the residual adhesion rate is likely to decrease. A:85%≦Residual adhesion rate B: Residual adhesion rate <85%
[0163] When the polyester film is used as a release film for producing a ceramic green sheet, taking into consideration the properties of a ceramic capacitor formed using the ceramic green sheet, the migration property is preferably rated as A or B, and more preferably rated as A.
[0164] <Windability> In the manufacturing process of each polyester film, when each film was wound into a roll, the presence or absence of wrinkles was visually confirmed, and the winding property was evaluated based on the following criteria. A rating of A is more preferable. A: There were no wrinkles on the roll. B: Wrinkles were present on the roll, but winding was successful.
[0165] [result] Table 1 shows the type and content of the composition used in the production of each polyester film, the results of each measurement, and the results of each evaluation.
[0166] [Table 1]
[0167] From the results shown in Table 1, it was confirmed that when the release layer did not contain either the silicone chain-containing cured material or the silicone chain-free cured material, the peel rate dependency was high (Comparative Example 1) or peeling was not possible (Comparative Example 2). On the other hand, it was confirmed that when the release layer contained a silicone chain-containing cured material and a silicone chain-free cured material, the peel rate dependency was low. From a comparison between Example 3 and Example 4, it was confirmed that when the thickness of the release layer was 2 to 65 nm, the peel rate dependency was lower and the winding property was superior. From a comparison between Example 3 and Example 4, it was confirmed that when the logarithmic decrement of the release layer is 0.05 or less, the peel rate dependency is lower and the winding property is more excellent. Comparing Example 1 with Examples 11 and 12, the surface free energy of the peeled surface was 16 mJ / m 2More than 30mJ / m 2 It was confirmed that when the thickness is less than 100 nm, the peel rate dependency is lower. A comparison between Example 3 and Example 9 confirmed that when the dynamic friction coefficient between the surface of the release layer opposite the polyester substrate and the surface furthest from the release layer is 0.2 or more, the winding properties are superior. From a comparison of Examples 10 and 11 with Examples 1, 6 and 7, it was confirmed that when the silicone chain-free cured product is a cured product of composition C containing one or more crosslinking agents selected from the group consisting of oxazoline compounds, carbodiimide compounds, and isocyanate compounds, and the ratio of the non-silicone resin content to the crosslinking agent content is 0.3 to 2.0, the migration property is superior.
Claims
1. A polyester film comprising a release layer and a polyester substrate, The release layer comprises a silicone chain-containing cured material and a silicone chain-free cured material.
2. 2. The polyester film according to claim 1, wherein the release layer has a thickness of 2 to 65 nm.
3. 3. The polyester film according to claim 1, wherein the release layer has a logarithmic decrement of 0.05 or less.
4. The surface free energy of the surface of the release layer is 16 mJ / m 2 30mJ / m or more 2 The polyester film according to claim 1 or 2, wherein the viscosity is less than 100 MPa.
5. 3. The polyester film according to claim 1, wherein the silicone chain-containing cured product is a cured product of a composition A containing a silicone compound having a vinyl group and a silicone compound having a SiH group.
6. 3. The polyester film according to claim 1, wherein the silicone chain-free cured product is a cured product of a composition C comprising one or more crosslinking agents selected from the group consisting of oxazoline compounds, isocyanate compounds, carbodiimide compounds, melamine compounds, and epoxy compounds.
7. 7. The polyester film of claim 6, wherein the composition C further comprises a non-silicone resin that crosslinks with the crosslinking agent.
8. The polyester film according to claim 7 , wherein the non-silicone resin comprises a resin selected from the group consisting of an acrylic resin, a urethane resin, and an olefin resin.
9. the silicone chain-free cured product is a cured product of a composition C containing one or more crosslinking agents selected from the group consisting of oxazoline compounds, carbodiimide compounds, and isocyanate compounds; 8. The polyester film according to claim 7, wherein a ratio of the content of the non-silicone resin to the content of the crosslinking agent is 0.3 to 2.
0.
10. 3. The polyester film according to claim 1 or 2, wherein the polyester substrate is substantially free of inorganic particles.
11. 3. The polyester film according to claim 1, wherein the release layer has a maximum protrusion height of 30 nm or less on the surface.
12. 3. The polyester film according to claim 1, which has a dynamic friction coefficient of 0.2 or more.
13. 3. The polyester film according to claim 1, which is used for producing a ceramic green sheet.
14. A method for producing a polyester film comprising a release layer and a polyester substrate, the method comprising the steps of: A method for producing a polyester film, comprising the step of applying a composition containing a component that forms a silicone chain-containing cured product and a component that forms a silicone chain-free cured product to one surface of the polyester substrate.
15. The method of claim 14 , wherein the composition comprises water.
Citation Information
Patent Citations
Silicone release polyester film
JP2021011081A